Enhancing Datagram Congestion Control Protocol for Efficient Long Delay Link - Shahrudin, Awang Nor (2012)
Most of the multimedia applications use the User Datagram Protocol (UDP) as a transport layer protocol because it is suitable for the delivery of multimedia data over the Internet. However, the use of UDP could endanger the stability of the network because there is no congestion control applied. To a certain extent, the network can collapse if too many applications deliberately use this protocol. Subsequently, instead of using the UDP, the applications have choices to use the Datagram Congestion Control Protocol (DCCP), which has a built-in congestion control that can provide a better network. Nevertheless, the congestion control mechanism in the CCID-2 TCP-like can cause problems when delivering multimedia data over a long delay link. To alleviate the problems, such as longer time taken for achieving maximum throughput, and throughput fluctuation during a congestion avoidance phase, two approaches have been used, i.e. setting of an appropriate slow-start threshold value and manipulating congestion window during a congestion avoidance phase. A new congestion control mechanism presented in this thesis, namely the "TCP-like Threshold Window (TCP-like TW)" is designed based on the advantages of the two approaches. It has been developed and modeled in the Network Simulator 2 (ns-2). The TCP-like TW has proven to enhance the performance of the DCCP when delivering multimedia data over long delay link networks, as well as over short delay. For a long delay link, the TCP-like TW congestion control mechanism is able to minimize the time taken to achieve the maximum throughput. It can smooth the fluctuation of throughput after achieving the maximum throughput. Furthermore, for the short delay link, the maximum throughput will be increased while maintaining the friendliness towards other congestion-controlled protocols.